2021
DOI: 10.1007/s00705-021-05258-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of SARS-CoV-2 in South America: demographic history and structuration signals

Abstract: In 2020, the emergence of SARS-CoV-2 caused a global public health crisis with significant mortality rates and a large socioeconomic burden. The rapid spread of this new virus has led to the appearance of new variants, making the characterization and monitoring of genetic diversity necessary to understand the population dynamics and evolution of the virus. Here, a population-genetics-based study was performed starting with South American genome sequences available in the GISAID database to investigate the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 78 publications
1
3
0
2
Order By: Relevance
“…Moreover, other minor forces are expected to increase diversity, such as co-circulation and population genetic admixture. These results are in congruence with other studies that showed statistically significantly negative values for neutrality tests [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, other minor forces are expected to increase diversity, such as co-circulation and population genetic admixture. These results are in congruence with other studies that showed statistically significantly negative values for neutrality tests [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…The genetic distance between the three SARS-CoV-2 clusters (Fst > 0.25) and low to intermediate gene flow (Nm) supports the clustering of the genetic diversity, with signs of gene flow between cluster A and B (Nm = 0.57) and between I and C (Nm = 0.36), but with low transfer of genetic diversity (Nm = 0.21) between cluster B and C due to extensive movement of hosts. A study in South America showed statistically significant values, indicating slight genetic differentiation [ 51 ]. Unlike the Fst, the other genetic differentiation estimators, Gst and Da, were underestimated due to the high mutation rate [ 33 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…These already-characterized mutations are present in variants being monitored, such as Mu and Zeta ( 7 , 30 , 31 ). It is important to mention that, given the variability of the amplified regions, we expect to detect more relevant mutations in future VoCs ( 16 , 44 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Si bien el pelaje de la mascota podría ser un vector pasivo (fómite), por adhesión de partículas virales expulsadas por una persona infectada en estornudos o saliva, aún no se ha reportado este tipo de transmisión. No obstante, la infección natural de SARS-CoV-2 en un nuevo huésped podría ocasionar cambios nucleotídicos de adaptabilidad evolutiva (44) que produzca posibles impactos negativos emergentes del virus (45), por lo cual es importante incluir estas secuencias encontradas en animales, dentro de la Red Regional de Vigilancia Genómica de COVID-19 para vigilar o predecir posibles variantes de interés (VOI) o variantes de preocupación (VOC) que llegasen a evolucionar en estos nuevos huéspedes a medida que aumenta su prevalencia (43,46) La mutación NSP12 S647I se ha eportado en secuencias de humanos en 80 países (47), incluido Colombia y particularmente Antioquia. Esta mutación, al estar extendida en la población humana, probablemente sea una adaptación evolutiva del virus en humanos y no una adaptación específica del virus en las células del gato, como se reportó con la mutación P323L presente en una secuencia de un gato infectado naturalmente en el Reino Unido (48).…”
Section: Discussionunclassified
“…Esta mutación, al estar extendida en la población humana, probablemente sea una adaptación evolutiva del virus en humanos y no una adaptación específica del virus en las células del gato, como se reportó con la mutación P323L presente en una secuencia de un gato infectado naturalmente en el Reino Unido (48). Además, esta mutación puede corresponder a una sustitución natural evolutiva, ya que la tasa de cambio de nucleótidos estimada para el SARS-CoV-2 varía entre 10 -3 y 10 -4 sustituciones por sitio y por año (46). Es necesario realizar estudios en otras regiones del genoma como la región codificante de la proteína S, en la cual, por ejemplo, la mutación D614G (compartida por los genomas felinos) confiere adaptabilidad en humanos y, por consiguiente, favorece la capacidad infecciosa del virus (49).…”
Section: Discussionunclassified